Tailor–made Covalent Organic‐Inorganic Polyoxometalate Hybrids: Versatile Platforms for the Elaboration of Functional Molecular Architectures. Issue 2 (22nd August 2016) - Izzet, Guillaume; Volatron, Florence; Proust, Anna
Abstract: Post‐functionalization of organically modified polyoxometalates (POMs) is a powerful synthetic tool to devise functional building blocks for the rational elaboration of POM‐based molecular materials. In this personal account we focus on iodoaryl‐terminated POM platforms, describe reliable routes to the synthesis of covalent organic‐inorganic POM‐based hybrids and their integration into advanced molecular architectures or multi‐scale assemblies as well as their immobilization onto surfaces. Valorisation of the remarkable redox properties of POMs in the fields of artificial synthesis and molecular electronic is especially considered. Abstract : Post–functionalization of organically modified polyoxometalates (POMs) is a powerful synthetic tool to devise functional building blocks for the rational elaboration of POM‐based molecular materials. In this personal account the authors focus on iodoaryl‐terminated POM platforms, describe reliable routes to the synthesis of covalent organic‐inorganic POM‐based hybrids and their integration into advanced molecular architectures or multi‐scale assemblies as well as their immobilization onto surfaces. Valorisation of the remarkable redox properties of POMs in the fields of artificial synthesis and molecular electronic is especially considered